2019
DOI: 10.1002/mame.201900316
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PLLA with High Ductility and Transparence by Blending with Tiny Amount of PVDF and Compatibilizers

Abstract: Poly(L‐lactic acid) (PLLA) with high ductility and transparence is fabricated by a blending tiny amount of polyvinylidene fluoride (PVDF) and reactive comb compatibilizers (RCC). Upon blending, the reaction between terminal carboxyl groups in PLLA and expoxy groups in RCC produces graft copolymer (PLLA‐g‐poly(methyl methacrylate) (PMMA)), which locates at the PVDF/PLLA interface due to the balanced stress on two sides. On the one hand, the PVDF domain size decreases remarkably with the help of compatibilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Blending PLA with renewable elastomers is one of the most economically attractive and scalable methods to achieve high-performance PLA materials. However, the poor compatibility between PLA and additive elastomers greatly limits these PLA/elastomer blends in achieving satisfying toughness. Adding block or graft copolymers as compatibilizers has been proven to be a highly efficient approach for improving the miscibility of the components in polymer blends. For example, Hillmyer and et al reported that the addition of polyethylene (PE)- b -poly (L-lactic acid) (PLLA) copolymers into PLLA/low-density polyethylene (LDPE) blends dramatically improved their toughness because of the enhancement of interfacial adhesion and the reduction of the LDPE particle size. , In PLA and other flexible biobased polyester blends, block copolymers containing the PLA block were also demonstrated to be highly efficient compatibilizers for improving the compatibility and performance of the blends, such as in the use of PLA- b -poly­(butylene succinate) (PBS) block copolymers for PLA/PBS blends, PLA- b -poly­(ε-caprolactone) (PCL) block copolymer for PLA/PCL blends, and so forth. However, most of the reports employed A- b -B block copolymers having the same chemical structure as the two blend components in these PLA-based blends. Because of lack of efficient synthesis methods, the preparation of A- b -B block copolymers is a great challenge for many PLA (A) and elastomer (B) blends. In addition, the A- b -B block copolymers are generally unsuitable for compatibilizing the PLA phase with other kinds of elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…Blending PLA with renewable elastomers is one of the most economically attractive and scalable methods to achieve high-performance PLA materials. However, the poor compatibility between PLA and additive elastomers greatly limits these PLA/elastomer blends in achieving satisfying toughness. Adding block or graft copolymers as compatibilizers has been proven to be a highly efficient approach for improving the miscibility of the components in polymer blends. For example, Hillmyer and et al reported that the addition of polyethylene (PE)- b -poly (L-lactic acid) (PLLA) copolymers into PLLA/low-density polyethylene (LDPE) blends dramatically improved their toughness because of the enhancement of interfacial adhesion and the reduction of the LDPE particle size. , In PLA and other flexible biobased polyester blends, block copolymers containing the PLA block were also demonstrated to be highly efficient compatibilizers for improving the compatibility and performance of the blends, such as in the use of PLA- b -poly­(butylene succinate) (PBS) block copolymers for PLA/PBS blends, PLA- b -poly­(ε-caprolactone) (PCL) block copolymer for PLA/PCL blends, and so forth. However, most of the reports employed A- b -B block copolymers having the same chemical structure as the two blend components in these PLA-based blends. Because of lack of efficient synthesis methods, the preparation of A- b -B block copolymers is a great challenge for many PLA (A) and elastomer (B) blends. In addition, the A- b -B block copolymers are generally unsuitable for compatibilizing the PLA phase with other kinds of elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , the morphology was significantly changed with the addition of FKM-AHA10 for 5 and 7 php, where the PVDF phase partly became a dispersed phase. At the same time, at high FKM-AHA10 loading, it may preferentially form micelles in the ENR50 domain rather than located at the interface. …”
Section: Resultsmentioning
confidence: 99%
“…Increasing the nHA wt% resulted in both decreasing UTS and elongation at the breakpoint. PLLA/PVDF blends showed improved ductility in the presence of compatibilizers [42]. COC in PLLA/COC10-nHA resulted in strong and ductile polymer; thus, its nanocom-posite with nHA showed elongation at breakpoint at higher strain percent values than PLLA/nHA.…”
Section: Mechanical Properties Of Nanocompositesmentioning
confidence: 99%